Comparing caregiver burden in owners of healthy dogs with and without limb amputation: a cross-sectional analysis - Pryjmak, Janine; Zablotski, Yury; Mille, Monika A.; Lauer, Susanne K. (Frontiers in Veterinary Science, 2026)
ObjectivesIn human medicine, limb amputation affects caregiver psychosocial burden. This study assessed caregiver burden in owners of dogs following limb amputation.Materials and methodsFrom March to September 2024, owners of healthy dogs with limb loss (> 6 months) and owners of healthy dogs without limb amputation (control dogs) were recruited via veterinary clinics, physiotherapy practices, university hospitals and social media to complete an online questionnaire. The 115-item survey included general questions on daily life and validated instruments assessing caregiver burden and psychosocial functioning: Zarit Burden Interview (ZBI), Perceived Stress Scale, Center of Epidemiologic Studies Depression scale, Generalized Anxiety Disorder 7-Item Scale, Quality of Life Enjoyment and Satisfaction Questionnaire. Descriptive statistics and group comparisons (Chi-Squared, Mann–Whitney U test and Students t-test) were performed in R.ResultsSeventy-six owners of dogs with limb amputation (hindlimb: n = 35; forelimb: n = 41) and 74 owners of control dogs completed the survey (90.7% women; 70.7% aged 19–49). ZBI and other scores did not differ significantly between groups. Caregiver demographics (age, gender, relationship status, profession, number of caregivers) and dog-related factors (age at amputation, reason, leg affected, size, weight, adoption status) showed no significant effect on ZBI-scores. Higher ZBI-scores were reported when dogs could no longer hike (p = 0.05), and lower scores when caregivers received positive social feedback (p = 0.02). Prosthesis use (p = 0.02), low prosthesis acceptance (p = 0.04) or use of assistive devices (p = 0.02) were associated with higher caregiver burden.ConclusionMost caregivers of canine amputees do not report elevated caregiver burden. However, functional changes in the dog and social or assistive factors were associated with caregiver experience.